Pembuatan Aplikasi Sistem Informasi Produksi pada PT. Rajapaksi Adyaperkasa - Evan Reinaldo; Alexander Setiawan; Tanti Octavia (Jurnal Infra, 2017)
PT. Rajapaksi Adyaperkasa is specialized in footwear production, at this time the company is difficult to know the production time and overhead expenses quickly. This leads to sometimes incorrect decision-making as it turns out that the new model produced has higher cost and took longer to produce than expected, causing some loss to the company.This application was created using Visual Basic .Net 2010 programming language and SQL Server 2012 database. Time data that has been gathered are tested with IBM SPSS Software. Time data that has been validated is used as the main core of this applicationThe final result of this application development is the company can know the time and cost of production of the shoe model with only seeing the shoe example, and existing shoe model data can be developed for making order and view the production schedule plan.